IDENTIFICATION OF URINARY METABOLITES OF PYRILAMINE AFTER ORAL-ADMINISTRATION TO MAN - CHUNG, BC; KIM, DH; JUNG, BH; EOM, K; SLIKKER, W; PARK, J (TAYLOR & FRANCIS LTD, 1994)
1. The metabolism of pyrilamine, 2-[4-methoxybenzyl-(2-dimethylaminoelhyl) amino] pyridine, was studied in adult male volunteers after a single oral dose of 50 mg. 2. Solvent extracts of urine obtained with or without enzyme hydrolysis were analysed by gc/ms after derivatization with MSTFA/TM SCI (N-methyl-N-trimethylsilyl-trifluoroacetamidel-trimethyl chlorosilane). The structure of metabolites were determined based on EI mass spectra and confirmed with those of authentic standards. 3. Conjugated metabolites identified in the urine were pyrilamine, O-desmethylpyril amine, and ring hydroxylated derivatives of pyrilamine. O-desmethylpyrilamine was also detected in low abundance as a free form. 4. These metabolites observed in human urine were quite different from those previously reported in rat.
Keywords: MALEATE; ANTIHISTAMINES; TRIPELENNAMINE; DRUGS; ASSAY; RAT